The right spouse : preferential marriages in Tamil Nadu - Clark-Decès, Isabelle, 1956-2017 (Stanford University Press, 2014)
The Right Spouse is an engaging investigation into Tamil (South Indian) preferential close kin marriages, so-called Dravidian Kinship. This book offers a description and an interpretation of preferential marriages with close kin in South India, as they used to be arranged and experienced in the recent past and as they are increasingly discontinued in the present. Clark-Decès presents readers with a focused anthropology of this waning marriage system: its past, present, and dwindling future. The book takes on the main pillars of Tamil social organization, considers the ways in which Tamil inter.